Productive restructuring, labor struggles and social actions in the current Brazil - Antunes, Ricardo (Estudios Latinoamericanos, 2019)
The neoliberal project, having in the productive restructuring of the capital its material base, assumed singular forms and caused that various capitalist countries reorganized theirs productive world, procuring to combine elements of the neoliberal ideology and dimensions of the productive restructuring of the capital. The quality control circles proliferated, constituted as groups of workers that they are incentivized by the capital to discuss the work and their performance with conferences to improve the productivity and the lucrative and the company. It is the new form that the capital uses to preempt of the savoir faire intellectual of the work. The worker must think and make by and for the capital, what deepens (contrarily to reduce) the subordination of the work to the capital. This trial is met to explain the form that adopts the capital in front to the work, and for its own reproduction, and offers a series of elements that explain the current standard of capitalist accumulation in so much presents the current state of the world of the work and its forms of organization through the union movement, as social and political movement. The author indicates the most important features of the occupational world: decrease of the manual worker; stressed increase in the new proletariat, of countless forms of subproletarianization or precariousness work; substantial increase in the feminine work; great expansion of medium salaried in the "services sector"; exclusion of the working youths and the "old" workers; escalation and superexplotation of the work of the immigrants, of the blacks, in addition to the expansion of the infantile work levels between others. The author emphasizes the challenges of the syndicalism in Brazil, what can transcend beyond this country, toward a project that it should, in its basic contours, to begin the disassembly of the standard of outstanding capitalist accumulation, through a set of measures that reject a globalization and an integration imposed by the logic of the capital, integrative for outside, for the capital and destructive and disintegrated for the workers.